Susceptibility of invasive tunicates Clavelina oblonga to reduced seawater salinities - Nina Majnarić; Dijana Pavičić-Hamer; Andrej Jaklin; Bojan Hamer (Aquaculture Reports, 2022)
The intensive colonial tunicate Clavelina oblonga invasion was observed in the summer of 2020 at shellfish farms located on the western and eastern coasts of the Istrian peninsula (NE, Adriatic, Croatia). Aquaculture facilities create an ideal environment for ascidians, therefore, as a possible environmentally friendly eradication measure, laboratory experimental exposure of C. oblonga to different reduced seawater salinities of 37, 30, 20 and 11 was examined in November 2020. During the total observation time (14 days exposure + 14 days of recovery at 37) at all seawater salinities, there was no sexual reproduction of Clavelina specimens and larvae settlement in general. Salinities of 37 and 30 didn’t provoke any significant effect in colonial corpus weight change and morphology. Salinities of 20 and 11 caused disorder in specimens feed uptake and feeding itself which led to change of colour, tissue necrosis and finally body fragmentation. Similar separate laboratory exposure of mussel Mytilus galloprovincialis specimens did not provoke significant differences in meat yield between control 37 salinity (14.0 %) and reduced salinities of 30 (14.2 %), 20 (14.6 %) and 11 (15.3 %) measured at the end of the recovery experiment. Based on our experimental results of C. oblonga salinity susceptibility and field observations (2020–2021), we can assume that field translocation of overgrown mussels and infrastructures to locations of seawater < 20 salinities could be a natural way for its eradication.